2004
DOI: 10.1038/ncb1117
|View full text |Cite
|
Sign up to set email alerts
|

Akt interacts directly with Smad3 to regulate the sensitivity to TGF-β-induced apoptosis

Abstract: Transforming growth factor beta (TGF-beta) induces both apoptosis and cell-cycle arrest in some cell lines, but only growth arrest in others. It is not clear how this differential response to TGF-beta is specified. Smad proteins are critical mediators of TGF-beta signalling. After stimulation by TGF-beta, Smad2 and Smad3 become phosphorylated by the activated TGF-beta receptor kinases, oligomerize with Smad4, translocate to the nucleus and regulate the expression of TGF-beta target genes. Here we report that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
285
5
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(316 citation statements)
references
References 28 publications
20
285
5
6
Order By: Relevance
“…However, both basal and TGFb-induced release of nuclear histones were inhibited in RIE/Evi1 cells relative to RIE/pBabe. We have previously reported that induction of apoptosis in RIE cells involves Smad3 (Conery et al, 2004), and, consistent with these data, RIE/dnSmad3 cells are resistant to induction of nuclear histone release by TGFb (Figure 4c). However, unlike Evi1, dnSmad3 had no effect on basal apoptosis in RIE cells.…”
Section: Evi1 Inhibits Tgfb-mediated Apoptosis In Intestinal Epithelisupporting
confidence: 90%
See 2 more Smart Citations
“…However, both basal and TGFb-induced release of nuclear histones were inhibited in RIE/Evi1 cells relative to RIE/pBabe. We have previously reported that induction of apoptosis in RIE cells involves Smad3 (Conery et al, 2004), and, consistent with these data, RIE/dnSmad3 cells are resistant to induction of nuclear histone release by TGFb (Figure 4c). However, unlike Evi1, dnSmad3 had no effect on basal apoptosis in RIE cells.…”
Section: Evi1 Inhibits Tgfb-mediated Apoptosis In Intestinal Epithelisupporting
confidence: 90%
“…We have shown that the apoptotic response to TGFb can be influenced by crosstalk between Smad3 and AKT (Conery et al, 2004), and several reports indicate that activation of PI3K/AKT signaling suppresses TGFbmediated apoptosis (Chen et al, 1998(Chen et al, , 1999Shih et al, 2000). Our data demonstrate that Evi1 activates PI3K/ AKT signaling, and suppresses TGFb-mediated apoptosis.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We thus hypothesized that the increased interaction of lithium-induced pCREB Ser133 with the transcriptional coactivators CBP/p300 concurrently suppresses Smad3/4-dependent gene transcription due to the sequestration of CBP/p300 by activated pCREB Ser133 . Recent studies demonstrate that AKT can directly interact with nonphosphorylated Smad3, promoting the sequestration of Smad3 in the cytoplasm and thereby impairing Smad3-dependent transcriptional activity (Conery et al, 2004;Remy et al, 2004). Although Smad3 phosphorylation is not affected by lithium treatment in cultured cortical neurons (unpublished data), we have not investigated whether lithium treatment alters AKTSmad3 interaction or Smad3 nuclear translocation.…”
Section: Discussionmentioning
confidence: 88%
“…PI 3-kinase in turn phosphorylates phosphatidylinositides on the 3' position to produce phosphatidylinositol 3,4-bisphosphate (PtdIns(3,4)P 2 and 3,4-triphosphate (PtdIns3,4)P 3 [46]. PtdIns(3,4)P 2 preferentially activates the Akt/PKB serine/ threonine kinase signaling pathway [4], which inactivates SMAD3 by sequestering unphosphorylated SMAD3 in the cytoplasm, thus preventing SMAD3 phosphorylation and nuclear translocation [6,37]. Sequestration of unphosphorylated SMAD3 inhibits TGFb1-induced, SMAD3-mediated transcription and apoptosis.…”
Section: Discussionmentioning
confidence: 99%